PELAKSANAAN KEGIATAN EKSTRAKURIKULER PADUAN SUARA DI SMPN 11 PADANG - Suci Aulia Dita; Hadi, Harisnal (Universitas Negeri Padang, 2025)
This research aims to describe and understand how the management and implementation of extracurricular choir activities at SMP Negeri 11 Padang are conducted. This type of research is qualitative with a descriptive approach. The research instrument is the researcher themselves, assisted by supporting instruments such as writing tools and a camera. Data is collected through literature study, observation, interviews, and documentation. The steps for analysing the data include gathering data, identifying data, classifying data, clarifying data, and describing data. The research results show that the planning of extracurricular choir activities at SMPN 11 Padang is carried out through several stages, namely first the coach prepares the choir members by recruiting them at the start of each new academic year, then setting a training schedule, followed by the coach preparing materials and selecting songs before starting practice. The implementation of the extracurricular choir activity is conducted by a trainer who always teaches the students individually according to their vocal qualification distribution, and during the delivery of material, the trainer demonstrates the melody and rhythm of the song sentence by sentence or phrase by phrase until the students understand and memorise the melody of the song material. At the end of each session, the trainer always provides an evaluation, informing them about the aspects that need improvement, and continuously reminding them about the importance of vocal techniques. Evaluatingn to evaluating the voices, the trainer also assesses the training process, urging the students to take each practice seriously, so the trainer does not have to repeatedly correct mistakes in that area.